2019
DOI: 10.1038/s41598-019-54410-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and Salivary Gland Dysfunction in the Non-obese Diabetic Mouse: Caveats for Preclinical Studies in Sjögren’s Syndrome

Abstract: the non-obese Diabetic (noD) mouse model for type i diabetes also develops some features of Sjögren's syndrome (SS). Since the source of the mice and the environment exert a strong influence on diabetes, this study investigated SS development in noD mice obtained from two vendors. female noD mice from the Jackson Laboratory (JAX) and taconic Biosciences were monitored for blood glucose and pilocarpine-induced salivation. The gut microbiome was analyzed by 16S rRNA sequencing of stool DnA. At euthanasia, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Hyperglycemia due to high blood glucose levels is a characteristic of diabetes, which causes many changes in the body through damage to various organs. Hyposalivation and submandibular gland dysfunction have been reported in in vivo models, especially in type 2 diabetic mice [26], non-obese diabetic mice [27], streptozotocin (STZ)-induced type 1 diabetic rats [28], and this study confirmed the improvement effect of polydatin on diabetes-induced hyposalivation in a type 2 diabetic db/db mice model.…”
Section: Discussionsupporting
confidence: 80%
“…Hyperglycemia due to high blood glucose levels is a characteristic of diabetes, which causes many changes in the body through damage to various organs. Hyposalivation and submandibular gland dysfunction have been reported in in vivo models, especially in type 2 diabetic mice [26], non-obese diabetic mice [27], streptozotocin (STZ)-induced type 1 diabetic rats [28], and this study confirmed the improvement effect of polydatin on diabetes-induced hyposalivation in a type 2 diabetic db/db mice model.…”
Section: Discussionsupporting
confidence: 80%
“…Although the initial NOD inbred (NOD/ShiLt) strain displayed symptoms resembling SS including the presence of inflammatory cell infiltrates and impaired salivary and lacrimal secretion, these animals also developed type I diabetes (T1D) (19,21). To circumvent the difficulties of studying SS in the background of T1D (27), we utilized a mouse model in which the NOD/ShiLt major histocompatibility complex was replaced with that of a healthy C57BL/10 strain, resulting in a congenic strain of mice (NOD.B10Sn-H2 b /J or NOD.B10) that develop pSS but are protected from T1D (16). Indeed, these animals share many clinical features associated with pSS including a female disease predilection, focal lymphocytic infiltration of the SMG and lacrimal glands, reduced salivary flow and systemic disease manifestations affecting the kidney and lung (17,(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative method measures the disease severity either as the area fraction covered by lymphocytic infiltrates (Allushi, Bagavant, Papinska, & Deshmukh, 2019) or as a focus score per 4 mm 2 salivary gland tissue (Fisher et al, 2017).…”
Section: Examine Salivary Gland Sectionsmentioning
confidence: 99%
“…They also develop salivary and lacrimal gland inflammation, show a drop in saliva production with increasing age, and are used as a SS model (Hu et al., 1992). However, glandular dysfunction in NOD mice correlates strongly with the level of hyperglycemia, a characteristic not common in patients with SS (Allushi et al., 2019). Thus, while glandular inflammation in NOD mouse may mimic that seen in patients, NOD mouse utility in investigating salivary gland dysfunction is open to debate.…”
Section: Commentarymentioning
confidence: 99%